Effect of cardiovascular fitness on performance metrics in Bangladeshi women cricket: a role-specific analysis employing the harvard step test - Farjana Akter Boby; Shaybal Chanda; Vinosh Kumar Purushothaman; Baby Salini; Swamynathan Sanjaykumar; Bekir Erhan Orhan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2024)
Background: Cardiovascular fitness is essential for sports performance, enabling players to endure intense training, delay fatigue, and reduce injury risk—all critical factors for achieving optimal results in competitive sports like cricket. Emphasizing inclusive health ensures that all athletes enhance their cardiovascular fitness and overall performance. Purpose: This study aimed to investigate the impact of cardiovascular fitness, assessed using the Harvard Step Test, on the performance indicators of Bangladeshi women cricketers across their respective playing roles. Method: 104 players, including 34 batters, 38 bowlers, and 32 all-rounders, were voluntarily selected from the “Bangladesh National Women’s Cricket League 2021-22”. Cardiovascular fitness was evaluated through the Harvard Step Test, and role-specific performance metrics such as strike rate, bowling economy, and dismissal rates were analyzed. Statistical analyses included descriptive statistics and one-way ANOVA to assess differences in aerobic fitness across player roles and correlation analyses to examine the relationships between performance metrics and Harvard Step Test scores. Results: The multi-group comparison did not reveal a statistically significant difference in aerobic fitness across the playing roles, F(2, 101) = 0.668, p = 0.515. Additionally, the Harvard Step Test scores showed a weak and statistically non-significant relationship with role-specific performance metrics: strike rate (r = 0.20, p = 0.06) for batters, bowling economy (r = -0.09, p = 0.51) for bowlers, and dismissals (r = 0.10, p = 0.38) for fielders. Conclusion: Cardiovascular efficiency is similar across batters, bowlers, and all-rounders among Bangladeshi women cricketers. The Harvard Step Test score is not directly associated with role-specific performance in women's cricket. These findings suggest that training programs should adopt a holistic physical fitness approach, incorporating role-specific training to enhance the overall abilities of female cricketers and contribute to the development of women's cricket in Bangladesh.